Memahami Kebijakan Ekonomi Politik Tiga Khalifah (Sebuah Kajian Historis Tiga Fase Peradaban Islam) - Ayief Fathurrahman (Universitas Islam Lamongan, 2018)
One thing that needs to be understood is that every result of human thought is always historical, tied to the space and time around it. The economic policies issued by Umar ibn Khatta>b, Umar ibn Abdul Azi>z and Ghazan Khan must have certain truths in accordance with the dimensions of space and the cycle of time. However, the form of policy is an effort to solve the problems of the State, especially the economic sector that occurred in the middle of their leadership period. This article aims to examine the political economic thought of three caliphs, namely Umar ibn Khatta>b, Umar ibn Abdul Azi>z, and Ghazan Khan with a historical approach. Political economic policy decided by Umar ibn Khatta>b, Umar ibn Abdul Azi>z, and Ghazan Khan has a character that is flexible. It means however its method, during its goal to create welfare for the people and not in conflict with al-Quran and al-Sunnah, then that policy is applied. This was apparent when some of their policies are not always same as Prophet’s policy, even differ from each other, but with that difference, the world has recorded them as a brilliant decision maker. The policy of the three caliphs teaches us the ultimate determinants of the economic policy of the meaning of welfare (maslahah) which form the basis of the formulation of one policy. Rigid economic system will only become a separate boomerang for economic growth itself. Because the true that the holy economic goal is not economic growth, but the welfare of mankind as perpetrators of economic activity in this hemisphere. Keywords: Islam, Economic-Politics, Flexible, Welfare